Women's Digital Activities During The 'Iddah Period: A Perspective Of Islamic Law And Social Media Reality - Shofiatul Jannah; Nindya Tri Wahyuni; Sholihatin Khofsah (FAKULTAS DAKWAH UIN SALATIGA, 2025)
Digital transformation has significantly reshaped social interaction patterns, including how Muslim women express themselves after divorce. The period of 'iddah, which is traditionally understood in Islamic law as a waiting period that restricts women's public presence and activity, now confronts new realities: women's virtual presence through digital platforms such as Instagram. This study aims to examine the digital activities of Muslim women during 'iddah by analyzing the cases of content creators Ria Ricis and Natalie Holscher, and to compare these practices with the classical jurisprudential views of the four major Sunni schools of thought. Employing a qualitative approach, this research uses literature analysis and case study methods, framed by the principles of maqāṣid al-sharī'ah and Islamic gender justice. The findings reveal that classical Islamic jurisprudence generally emphasizes restrictions on women's mobility and appearance during 'iddah, yet offers no explicit guidance on digital behavior in modern contexts. Meanwhile, the digital practices of the selected figures do not necessarily contradict Islamic ethical values, especially when driven by productive motives and conducted within the bounds of modesty. Therefore, this study argues for a contextual and gender-sensitive reinterpretation of Islamic law to respond to the evolving digital realities faced by contemporary Muslim women.